La opinión de nuestro alumnado sobre los métodos de enseñanza y sistemas de evaluación empleados en la especialidad de Educación Física de los estudios de Magisterio - Edmundo Loza Olave (Universidad de La Rioja, 2013)
This text tries to carry out, through an anonymous questionnaire answered by the students of Physical Education, a study of the teaching methodology and teacher evaluation systems used by the teachers in the Teacher Training Schools and Educational Faculties. In order to know not only the demands and interests of our students, but their opinion of the teaching-learning process carried out in the Teacher Training Schools. To get this aim we have done a research, that it can be inserted in the current educational investigatíon trends, whose purpose is to offer information about a given educational situation. This research also tries to take into account the different aspects involved, so that its fundamental dimension is descriptive, but afterwards it will also allow to carry out valuations and proposals of evaluation.